Needs Analysis of the TGT Learning Model Assisted by Wordwalls in Developing Critical Thinking in Elementary School Student - Riana, Herlyna Desi; Hidayat, Wahyu; Zhanty, Luvy Sylviana; Syafitri, Adiarni Decintya (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
This research is motivated by the fact that early reading and writing learning is still conventional. Reading and writing skills are very important in developing critical thinking skills as part of 21st-century competencies since the first grade of elementary school. This study analyzes how the Teams Games Tournament (TGT) learning model assisted by Wordwall can be used in developing critical thinking skills in first-grade students. In this study, a qualitative descriptive method was used. 20 first-grade teachers in Padalarang District served as respondents. Data were collected through an open-ended questionnaire and analyzed using the method developed by Miles and Huberman, including presentation, drawing conclusions, and data reduction. The results showed that 100% of teachers stated that early reading and writing skills are very important, but each teacher also experienced difficulties in implementing them. 80% stated that students have a strong drive to learn. 90% understood the TGT model, and 60% had implemented it. 95% had an understanding of the concept of critical thinking and believed that TGT can help students think critically. 80% have used learning applications, 90% stated that the development of application-assisted TGT is necessary, and 100% agreed that the implementation of Wordwall-assisted TGT is very important. The novelty of this study focuses on evaluating the need for Wordwall-assisted TGT in first-grade students who are still in the early literacy stage. The results of the study indicate the importance of implementing digital-based interactive learning models to improve basic literacy and critical thinking skills from an early age.